PENATALAKSANAAN ARTHRITIS RHEUMATOID PADA LANJUT USIA DI PANTI SOSIAL TRESNA WERDHA BUDI LUHUR JAMBI - Ariyanto Ariyanto; Tina Yuli Fatmawati (Jurnal Abdimas Kesehatan (JAK), 2019)
Rheumatoid arthritis is a chronic systemic inflammatory disease that attacks several joints, the synovium, which occurs in the inflammatory process that causes damage to the joints. The problem faced by partners is that most elderly people still do not understand rheumatism management properly such as a healthy diet, the importance of maintaining body weight to avoid obesity and have not understood traditional rheumatoid management with lemongrass therapy. This community service activity has been conducted at the Tresna Werdha Social Institution in Jambi City in December 2018. The method used a survey, lecture, discussion, demonstration / simulation approach. The results achieved are the implementation of health counseling in the elderly about rheumatoid management, demonstration of lemongrass therapy therapy and conducting pain scale measurements before and after therapy